Improving Survival of Disassociated Human Embryonic Stem Cells by Mechanical Stimulation Using Acoustic Tweezing Cytometry - Chen, Di (Biophys J, 2015)
Dissociation-induced apoptosis of human embryonic stem cells (hESCs) hampers their large-scale culture. Herein we leveraged the mechanosensitivity of hESCs and employed, to our knowledge, a novel technique, acoustic tweezing cytometry (ATC), for subcellular mechanical stimulation of disassociated single hESCs to improve their survival. By acoustically actuating integrin-bound microbubbles (MBs) to live cells, ATC increased the survival rate and cloning efficiency of hESCs by threefold. A positive correlation was observed between the increased hESC survival rate and total accumulative displacement of integrin-anchored MBs during ATC stimulation. ATC may serve as a promising biocompatible tool to improve hESC culture.